Characterizing farm households in Western Bangladesh through a quantitative farming systems typology - Jahanara, Ishrat; Zepeda, Adair; Cheesman, Stephanie; Babu, T.S.; Karki, Saral; Hossain, Khaled; Ahmed, Sharif; Bhandari, Humnath; Gathala, Mahesh; Krupnik, Timothy J.; López Ridaura, Santiago (International Maize and Wheat Improvement Center, 2023)
The Sustainable Intensification of Mixed Farming Systems (SIMFS) is a CGIAR initiative. This initiative ‘aims to provide equitable, transformative pathways for improved livelihoods of actors in mixed farming systems through sustainable intensification within target agroecological and socioeconomic settings. To achieve this, different methodologies, innovations, and practices have been implemented to understand and improve the agroecological/productive conditions to assess a benefit on nutrition, food security and welfare. SIMFS works closely with the CGIAR Regional Integrated Initiative on Transforming Agrifood Systems in South Asia (TAFSSA) that propels evidence into impact through engagement with public and private partners across the production-to-consumption continuum, to achieve productive, environmentally sound South Asian agrifood systems that support equitable access to sustainable healthy diets.